The Role of Laparoscopic Cholecystectomy After Severe and/or Necrotic Pancreatitis in the Setting of Modern Minimally Invasive Management of Pancreatic Necrosis. Issue 7 (August 2020) - Ackermann, Travis G.; Cashin, Paul A.; Alwan, Mostafa; Wewelwala, Chamila C.; Tan, Darius; Vu, Anh N.; Bowers, Kaye A.; Berry, Roger; Croagh, Daniel G.
Abstract : Objectives: The trend toward minimally invasive procedures (MIP) in necrotizing pancreatitis is increasing. The optimal timing and technique of cholecystectomy in severe/necrotizing pancreatitis is unclear. This study aims to determine the role of laparoscopic cholecystectomy after severe/necrotizing pancreatitis in the context of MIP. Methods: Retrospective analysis of a prospective database was performed for consecutive patients after cholecystectomy for gallstone pancreatitis between January 2011 and January 2018 at Monash Health, Melbourne, Australia. Results: Three hundred fifty-five patients with gallstone pancreatitis underwent laparoscopic cholecystectomy with 2 conversions. Patients with severe pancreatitis were older ( P = 0.002), with a more even sex distribution when compared with mild pancreatitis. Females predominated in the mild pancreatitis group. Patients with moderate/severe pancreatitis ( P = 0.002) and necrosis ( P > 0.001) were more likely to have delayed cholecystectomy compared with mild pancreatitis. There was no increase in biliary presentations while awaiting cholecystectomy. Length of stay for patients with severe/necrotizing pancreatitis ( P = 0.001) was increased, surgical complications appeared similar. Conclusions: Laparoscopic cholecystectomy can be performed safely and effectively for pancreatitis, irrespective of severity. The paradigm shift in the management of severe necrotizing pancreatitis away from open necrosectomy toward MIP can be extended to encompass laparoscopic cholecystectomy.